Openings and Exits in Community HIV Prevention: Exploring Stages of Community-Academic Partnerships - Dill, LeConté J. (Health Promot Pract, 2019)
Barbershop-based interventions have been increasingly implemented as a means to support culturally-relevant and community-accessible health promotion and disease prevention efforts. Specifically, in neighborhoods of Brooklyn, NY with high HIV seroprevalence rates, barbers have volunteered to support an initiative to help reduce sexual risk behavior. After implementing the Barbershop Talk with Brothers program for five years, we explored how program participation has impacted barbers’ HIV prevention and counseling skills to promote their clients’ health, and assessed their views of next stages of the community academic partnership, once the specific project ended. Through employing rigorous qualitative research methods with personnel at participating barbershops, key results include that although barbers self-identify as community leaders and even as health educators, they want ongoing support in educating customers about other topics like nutrition and physical activity, including upstream social determinants of health, such as housing and employment. They are also concerned regarding how best to support continuity of efforts and maintenance of partnerships between projects. These findings provide insight toward adjourning community-based participatory research projects, which can inform other academic researchers, organizations, and businesses who partner with community members.